Surgical Site Infection in Cesarean Section Operation: Risk and Management - Riad N. Younes; Tayna F. Farias; Rodrigo A.S. Sardenberg (International Journal of Infection Prevention, 2019)
Cesarean sections (CS) are one of the most commonly performed surgical procedures worldwide. There is great variability in the percentage of cesarean sections between countries, varying from 3% to 42.9%5. In the US, approximately 32% of deliveries occur through a cesarean section. Overall, a drastic increase in cesarean section rate has been reported reaching its highest level at the present time. In Brazil, considering the types of births by live births from 2006 to 2016, the national percentage of cesarean section was 52.37%. The variability in this percentage can still be perceived within Brazilian territory. The highest cesarean rate occurred in the Southern region, representing 58.33% of births, while the lowest rate occurred in the Northern region, with 41.79%. It is possible to see the steady increase in the percentage of CS over time, from 45.01% in 2006 to 55.39% in 2016.
Keywords: Cesarean